Assessing the urinary concentration of nitrofurantoin and its antibacterial activity against Escherichia coli, Staphylococcus pseudintermedius, and Enterococcus faecium isolated from dogs with urinary tract infections - Hung, Chien-Che; Varga, Csaba; Reinhart, Jennifer M.; Maddox, Carol W.; Dilger, Ryan N.; Forsythe, Lauren; Stevenson, Amy K.; Franklin-Guild, Rebecca J.; Paul, Narayan C.; Ramachandran, Akhilesh (Frontiers in Veterinary Science, 2023)
Nitrofurantoin, a broad-spectrum nitrofuran class antibiotic, is empirically applied as a first-line antibiotic in treating human urinary tract infections (UTIs) due to its great efficacy and high achievable concentration. The interest in using this antibiotic in companion animals has increased due to the growing demand for effective antibiotics to treat UTIs caused by multidrug-resistant bacteria. Currently, the susceptibility interpretations for nitrofurantoin are based on the breakpoints set for humans, while the canine-specific breakpoints are still unavailable. In this study, we assessed the concentration of nitrofurantoin reaching the dog’s urine using the recommended oral dosing regimen. In addition, we examined the efficacy of this breakpoint concentration against the common canine UTI pathogens, Escherichia coli, Staphylococcus pseudintermedius, and Enterococcus faecium. Eight experimental beagle dogs were treated with ~5 mg/kg of nitrofurantoin macrocrystal PO 8qh for 7 days. The urine samples were collected via cystocentesis at 2, 4, and 6 hours after administration on day 2 and day 7 and used to quantify nitrofurantoin concentrations by ultra-high performance liquid chromatography. The results showed that 26.13-315.87 µg/mL nitrofurantoin was detected in the dogs’ urine with a mean and median concentration of 104.82 and 92.75 µg/mL, respectively. Additionally, individual dogs presented with urinary nitrofurantoin concentrations greater than 64 µg/mL for at least 50% of the dosing intervals. This concentration efficiently killed E. coli, and S. pseudintermedius, but not E. faecium strains carrying an MIC90 value equal to 16 µg/mL, 16 µg/mL, and 128 µg/mL, respectively. Taken together, these results suggest that the value of 64 µg/mL may be set as a breakpoint against UTI pathogens, and nitrofurantoin could be an effective therapeutic drug for empiric therapy against E. coli and Staphylococcus pseudintermedius for canine UTIs.